Diary of a wimpy kid : the ugly truth - Kinney, Jeff (USA : Amulet, 2011)
While trying to find a new best friend after feuding with Rowley, middle-school slacker Greg Heffley is warned by older family members that adolescence is a time to act more responsibly and to think seriously about his future.
Keywords: Summer-Fiction; Diaries-Fiction; Humorous stories-Fiction